Stepped-Frequency Radar Sensors Theory, Analysis and Design - Nguyen, Cam.; Park, Joongsuk; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents the theory, analysis and design of microwave stepped-frequency radar sensors. Stepped-frequency radar sensors are attractive for various sensing applications that require fine resolution. The book consists of five chapters. The first chapter describes the fundamentals of radar sensors including applications followed by a review of ultra-wideband pulsed, frequency-modulated continuous-wave (FMCW), and stepped-frequency radar sensors. The second chapter discusses a general analysis of radar sensors including wave propagation in media and scattering on targets, as well as the radar equation. The third chapter addresses the analysis of stepped-frequency radar sensors including their principles and design parameters. Chapter 4 presents the development of two stepped-frequency radar sensors at microwave and millimeter-wave frequencies based on microwave integrated circuits (MICs), microwave monolithic integrated circuits (MMICs) and printed-circuit antennas, and discussestheir signal processing. Chapter 5 provides the electrical characterization and test results of the developed microwave and millimeter-wave stepped-frequency radar sensors. Finally, a summary and conclusion is provided.
Introduction -- General Radar Sensor Analysis -- Stepped-Frequency Radar Sensor Analysis -- Development of Stepped-Frequency Radar Sensors -- System Characterization and Tests -- Summary and Conclusions.
Keywords: Telecommunication; Electronic circuits; Electronics; Microwaves, RF Engineering and Optical Communications; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation